Do Mantle Cell Lymphomas have an “Achilles Heel”? - Saba, Nakhle (2014)
PURPOSE OF REVIEW: Mantle cell lymphoma (MCL) is a mature B-cell malignancy that continues to have a high mortality rate. In this manuscript we discuss key pathogenic pathways in MCL biology and their possible therapeutic targeting. RECENT FINDINGS: In addition to Cyclin-D1 the transcription factor SOX-11 emerged as a common characteristic of MCL. Genomic studies have identified a number of recurrently mutated genes; in order of descending frequency these include ATM, CCND1, UBR5, TP53, BIRC3, NOTCH1/2 and TRAF2. However, no clear oncogenic driver has been identified. In contrast, several observations indicate that MCL cells are antigen-experienced cells and that the tumor microenvironment and B-cell receptor engagement are important. This is underscored by the impressive clinical responses achieved with the BTK inhibitor ibrutinib. Recently identified activating mutations in the non-canonical NF-κB pathway could give rise to ibrutinib resistance. PARP and aurora kinase inhibitors may be synthetic lethal with the common aberrations in DNA damage pathways found in MCL. Also, ABT-199, a potent and selective inhibitor of BCL-2 has promising activity in early studies. SUMMARY: MCL is a heterogeneous disease and no single Achilles heel has been identified. Nevertheless, genomic, molecular, and clinical studies have revealed vulnerabilities that can be exploited for effective therapy.